Global spillovers from multi-dimensional US monetary policy - Georgios Georgiadis; Marek Jarociński (European Central Bank (ECB), 2023)
We estimate spillovers from US monetary policy for different measures in the Federal Reserve's toolkit. We make use of novel measures of exogenous variation in conventional rate policy, forward guidance and large-scale asset purchases (LSAPs) based on high-frequency asset-price surprises around Federal Open Market Committee meetings. The identification relies on relatively weak assumptions and accounts for the possible presence of residual endogenous components-such as central bank information effects-in these monetary policy surprises. We find that: (i) forward guidance and LSAPs trigger much larger spillovers than conventional rate policy; (ii) spillovers transmit predominantly through financial channels centering on global investors' risk appetite and manifest in changes in equity prices, bond spreads, capital flows and the dollar exchange rate; (iii) LSAPs trigger immediate international portfolio re-balancing between US and advanced-economy bonds, but generally entail only rather limited term premium spillovers; (iv) both forward guidance and LSAPs entail trade-offs for emerging-market-economy central banks, either between stabilizing output and prices or between additionally ensuring financial stability in terms of capital inflows.
Keywords: F42; E52; C50; 330; Monetary policy spillovers; US monetary policy shocks; central bank information effects; high-frequency identification